2017
DOI: 10.1039/c7cp03335d
|View full text |Cite
|
Sign up to set email alerts
|

Structural assignment of small cationic silver clusters by far-infrared spectroscopy and DFT calculations

Abstract: The structures of small cationic silver clusters Ag (n = 3-13) are investigated by comparing measured far-infrared multiple photon dissociation spectra of cluster-argon complexes with the calculated harmonic vibrational spectra of different low-energy structural isomers. A global structure search was carried out using the CALYPSO structure prediction method, after which isomers were locally optimized with the meta GGA functional TPSS. The obtained structures of the cationic silver clusters are mostly consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 44 publications
3
26
0
Order By: Relevance
“…For instance, it is now known that neutral Au20 adopts a tetrahedral (pyramidal) structure [10,11,12], and that anionic gold clusters form hollow cages [13]. The relativistic character of gold [14] is manifested when comparing the predicted and experimentally observed structures of Au clusters with those of Cun and Agn [15,16]. While Cu and Ag clusters adopt 3D structures from n = 5, Au clusters retain planar geometries up to significantly larger n.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is now known that neutral Au20 adopts a tetrahedral (pyramidal) structure [10,11,12], and that anionic gold clusters form hollow cages [13]. The relativistic character of gold [14] is manifested when comparing the predicted and experimentally observed structures of Au clusters with those of Cun and Agn [15,16]. While Cu and Ag clusters adopt 3D structures from n = 5, Au clusters retain planar geometries up to significantly larger n.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 On the other hand, for cationic silver clusters it has been suggested that the dimensional transition occurs already for Ag + 5 , which has a 2D structure with a slightly lower energy than the 3D one, while Ag + 6 and Ag + 7 display lowest energy 3D structures. 39,107 Anyway, this is a quite difficult problem because experimentally it is not trivial to distinguish clusters of the same size but different dimensionality. A computational support is thus required.…”
Section: D-3d Crossovermentioning
confidence: 99%
“…The authors stated that these effects are attributed to symmetry breaking, which enhances electron density polarization of the cobalt clusters induced by Ar tagging. This strong effect of Ar addition is markedly different from other, larger, metal clusters, such as cationic niobium, tantalum, and silver clusters, in which the influence of the rare-gas atoms on the IRMPD spectra was found to be small and limited to frequency shifts of a few wavenumbers only [52][53][54]. Co4 + and Co5 + were previously studied by Fielicke and co-workers [16], who reported IRMPD spectra for Co4Ar1,2,4,5 + and Co5Ar1,5 + .…”
Section: The Vibrational Spectra Of Argon Complexes Conarm + and Con-mentioning
confidence: 65%